Identification of the sites of tau hyperphosphorylation and activation of tau kinases in synucleinopathies and Alzheimer's diseases. - Valeriy Duka; Jae-Hoon Lee; Joel Credle; Jonathan Wills; Adam Oaks; Ciaran Smolinsky; Ketul Shah; Deborah C Mash; Eliezer Masliah; Anita Sidhu (PLoS ONE)
Objective Most neurodegenerative diseases contain hyperphosphorylated Tau [p-Tau]. We examined for the first time epitopes at which Tau is hyperphosphorylated in Parkinson's disease, dementia with Lewy bodies and Alzheimer's disease, and also select Tau kinases. Methods Postmortem frontal cortex from Parkinson's disease, dementia with Lewy bodies, Alzheimer's disease and striata from Parkinson's disease, were analyzed by immunoblots using commercially available antibodies against 20 different phospho-epitopes of Tau. Major Tau kinases were also screened. Results in diseased tissues were compared to nondiseased controls. Results In Alzheimer's disease, Tau was hyperphosphorylated at all the 20 epitopes of p-Tau. In dementia with Lewy bodies, p-Tau formation occurred at 6 sites sharing 30% overlap with Alzheimer's disease, while in Parkinson's frontal cortex, an area which does not degenerate, Tau hyperphosphorylation was seen at just 3 epitopes, indicating 15% overlap with Alzheimer's disease. In Parkinson's disease striatum, an area which undergoes considerable neurodegeneration, Tau was hyperphosphorylated at 10 epitopes, sharing 50% overlap with Alzheimer's disease. Between frontal cortex of Parkinson's disease and dementia with Lewy bodies, there were only two p-Tau epitopes in common. In striata of Parkinson's disease, there were 3 clusters of Tau hyperphosphorylated at 3 contiguous sites, while two such clusters were detected in dementia with Lewy bodies; such clusters disrupt axonal transport of mitochondria, cause microtubule remodeling and result in cell death. p-GSK-3β, a major Tau kinase, was activated in all brain regions examined, except in dementia with Lewy bodies. Activation of other Tau kinases was seen in all brain regions, with no clear pattern of activation. Interpretation Our studies suggest that the three neurodegenerative diseases each have a signature-specific profile of p-Tau formation which may be useful in understanding the genesis of the diseases and for the development of a panel of specific biomarkers.